When Dicty Met Myco, a (Not So) Romantic Story about One Amoeba and Its Intracellular Pathogen - Cardenal-Muñoz, Elena; Barisch, Caroline; Lefrançois, Louise H.; López-Jiménez, Ana T.; Soldati, Thierry (Frontiers in Cellular and Infection Microbiology, 2018)
In recent years, Dictyostelium discoideum has become an important model organism to study the cell biology of professional phagocytes. This amoeba not only shares many molecular features with mammalian macrophages, but most of its fundamental signal transduction pathways are conserved in humans. The broad range of existing genetic and biochemical tools, together with its suitability for cell culture and live microscopy, make D. discoideum an ideal and versatile laboratory organism. In this review, we focus on the use of D. discoideum as a phagocyte model for the study of mycobacterial infections, in particular Mycobacterium marinum. We look in detail at the intracellular cycle of M. marinum, from its uptake by D. discoideum to its active or passive egress into the extracellular medium. In addition, we describe the molecular mechanisms that both the mycobacterial invader and the amoeboid host have developed to fight against each other, and compare and contrast with those developed by mammalian phagocytes. Finally, we introduce the methods and specific tools that have been used so far to monitor the D. discoideum - M. marinum interaction.